The IMF and the force of History : Ten Events and Ten Ideas that Have Shaped the Institution - Boughton, James (IMF Working Papers; Working Paper, 2004)
The International Monetary Fund was designed during World War II by men whose worldview had been shaped by the Great War and the Great Depression. Their views on how the postwar international monetary system should function were also shaped by their economics training and their nationalities. After the IMF began functioning as an institution, its evolution was similarly driven by a combination of political events (Suez, African independence, the collapse of global communism), economic events (the rising economic power of Europe, the Middle East, and Asia), and trends and cycles in economic theory (the monetary approach to the balance of payments, new classical economics, the rise and fall of the Washington Consensus). As they happened, these forces had effects that were perceived as adaptations to current events and new ideas within a fixed institutional structure and mandate. The cumulative effect of history on the institution has been rather more profound and requires a longer and larger perspective.